PRINCIPLES OF PRUDENTIAL IN IFRS FINANCIAL STATEMENTS AND ITS EFFECT ON EARNINGS RESPONSE COEFFICIENT AND PROFIT MANAGEMENT - Suryani, Arna; Herianti, Eva (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
The purpose of this study is to determine the effect of prudential principle of financial statements in IFRS on earnings response coefficients and profit management of manufakturing companies. This study uses analytical methods Partial Least Square (PLS) through analisys software called Smart PLS 2.0 M3. The object of this research is manufacturing companies in Indonesia with a total of 57 analysis unit manufacturing company during the period from 2013 to 2015.Based on the results of the study, it is obtained the following findings: the precautionary of financial principle is proven to have a significant positive effect on the earnings response coefficient. The prudential financial principle is proven to have significant harmful impact on earnings.Manajemen is proved to have significant positive effect on banking principles prudential reports. Then, precautionary principle financial statements have greater direct influence on earnings response coefficients.This study has implications both theoretically and manajerial. The theoretical implication, the study makes an important contribution in the development of the theory of the precautionary principle financial statements, earnings response coefficients and earnings management. Managerial implications, this research has implications for users of financial statements in taking decision that is not only based on accounting figures, but also need to look at the quality of earnings presented. The precautionary principle financial statements required to reduce opportunistic earnings management so as to improve the quality of earnings and designated by increased earnings response coefficients. Keywords: Principle of Prudence, Financial Statement, Earnings Response Coefficient, Profit Management